2016
DOI: 10.1111/jvh.12507
|View full text |Cite
|
Sign up to set email alerts
|

Public health clinic‐based hepatitis C testing and linkage to care in baltimore

Abstract: Background Testing and linkage to care are important determinants of hepatitis C virus (HCV) treatment effectiveness. Public health clinics serve populations at high risk for HCV. We investigated their potential to serve as sites for HCV testing, initiation of and linkage to HCV care. Methods Cross-sectional study of patients accessing Sexually Transmitted Infections (STI) care at the Baltimore City Health Department (BCHD) STI clinics, from June 2013 through April 2014. Logistic regression was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 37 publications
5
49
4
1
Order By: Relevance
“…Simplified HCV testing, including dried blood spot testing (McAllister et al, 2014) and point-of-care HCV testing (Bottero et al, 2015; Morano et al, 2014) has been shown to facilitate linkage to HCV care. Other strategies that have been demonstrated to facilitate linkage to HCV care and treatment include, non-invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care (Foucher et al, 2009; Marshall et al, 2015; Moessner et al, 2011), integrated HCV care (Cullen et al, 2006; Evon et al, 2011; Ho et al, 2015; Knott et al, 2006; Masson et al, 2013; Zhou et al, 2016), patient navigation programs (Falade-Nwulia et al, 2016; Trooskin et al, 2015), and telemedicine (Arora et al, 2011; Lloyd et al, 2013; Mashru, Kirlew, Saginur, & Schreiber, 2017; Tahan, Almashhrawi, Kahveci, Mutrux, & Ibdah, 2016). …”
Section: Linkage To Hcv Care and Treatmentmentioning
confidence: 99%
“…Simplified HCV testing, including dried blood spot testing (McAllister et al, 2014) and point-of-care HCV testing (Bottero et al, 2015; Morano et al, 2014) has been shown to facilitate linkage to HCV care. Other strategies that have been demonstrated to facilitate linkage to HCV care and treatment include, non-invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care (Foucher et al, 2009; Marshall et al, 2015; Moessner et al, 2011), integrated HCV care (Cullen et al, 2006; Evon et al, 2011; Ho et al, 2015; Knott et al, 2006; Masson et al, 2013; Zhou et al, 2016), patient navigation programs (Falade-Nwulia et al, 2016; Trooskin et al, 2015), and telemedicine (Arora et al, 2011; Lloyd et al, 2013; Mashru, Kirlew, Saginur, & Schreiber, 2017; Tahan, Almashhrawi, Kahveci, Mutrux, & Ibdah, 2016). …”
Section: Linkage To Hcv Care and Treatmentmentioning
confidence: 99%
“…Better outcomes were found among opioid users undergoing substance abuse treatment, where 71% of persons with chronic HCV infection initiated treatment . In addition, a study in a Baltimore sexually transmitted infections clinic found high linkage to care rates among persons who were referred to off‐site specialists, with the assistance of patient navigation …”
mentioning
confidence: 99%
“…In this sample of primary care providers in a region with high HCV prevalence [9,1719], a large proportion of PCPs were aware of new HCV treatments and agreed that treatment would benefit the communities they serve. However, only 22% of PCPs agreed that in the era of interferon-free, direct-acting regimens, HCV treatment should be provided by PCPs, and they were statistically more likely to have a high prevalence of HCV and have patient support services in their clinics.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to significant delays in or failure of HCV care linkage due to a combination of patient and provider level factors including long specialist wait times or lack of willingness by patients to attend HCV care appointments at alternate venues [6,9]. Newly approved and highly effective direct acting antivirals (DAA) make it possible for HCV to be cured with low patient and provider burden and has raised the possibility of HCV elimination in the US [10].…”
Section: Introductionmentioning
confidence: 99%